Galaxies. - World Book, Inc. (Chicago : World Book, 2010)
"An introduction to galaxies with information about their formation and characteristics. Includes diagrams, fun facts, glossary, resource list, and index"--Provided by publisher.
Includes index.
Keywords: Galaxies -- Juvenile literature